2016
DOI: 10.5551/jat.33225
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure as a Comorbidity of Diabetes: Role of Dipeptidyl Peptidase 4

Abstract: Heart failure is a primary cause of death worldwide, and it is notable that heart failure patients exhibit a high incidence of diabetes. On the other hand, comorbid diabetes significantly worsens the prognosis of heart failure, even independently of complicated coronary artery disease.To date, heart failure caused by diabetes has been designated as "diabetic cardiomyopathy (DMC)," and a recent cohort study of the large-scale (1.9 million people) research platform of linked electronic medical records in UK (CAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
9
0
1
Order By: Relevance
“…As recently reviewed, evidence shows that in animal models, DPP4 inhibitors have antifibrotic effects in the heart and kidneys. As recently reviewed by Fadini et al, however, the reality is that the putative cardiorenal protective effects of DPP4 inhibitors detected in some preclinical models have not been borne out in large randomized clinical trials, observational studies, or meta‐analyses.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed, evidence shows that in animal models, DPP4 inhibitors have antifibrotic effects in the heart and kidneys. As recently reviewed by Fadini et al, however, the reality is that the putative cardiorenal protective effects of DPP4 inhibitors detected in some preclinical models have not been borne out in large randomized clinical trials, observational studies, or meta‐analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The cleaved dipeptides are bioactive molecules regulating the cardiovascular system as well. Dpp4 inhibitors have been reported to be cardioprotective in most of the preclinical and clinical studies in T2DM [ 73 ]. In contrast, some cardiovascular outcome studies revealed increased hospitalization rates for heart failure among a subset of DPP4 inhibitor-treated diabetic subjects [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important pathophysiological mechanisms in progression to heart failure in diabetes is the increased risk of hypertension, which leads to increased afterload and pressure overload, eventually volume overload [25]. Interestingly, dipeptidyl peptidase-4 (DPP4), a key enzyme that regulates glucose metabolism has been reported as a potential biomarker in the diagnosis of diastolic heart failure in the patients of diabetic cardiomyopathy, further substantiating the pivotal role of glucose dysregulation in diabetic cardiomyopathy [27]. …”
Section: Diabetic Cardiomyopathy and Heart Failurementioning
confidence: 99%